If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5w + -1)(6w + 3) = 0 Reorder the terms: (-1 + 5w)(6w + 3) = 0 Reorder the terms: (-1 + 5w)(3 + 6w) = 0 Multiply (-1 + 5w) * (3 + 6w) (-1(3 + 6w) + 5w * (3 + 6w)) = 0 ((3 * -1 + 6w * -1) + 5w * (3 + 6w)) = 0 ((-3 + -6w) + 5w * (3 + 6w)) = 0 (-3 + -6w + (3 * 5w + 6w * 5w)) = 0 (-3 + -6w + (15w + 30w2)) = 0 Combine like terms: -6w + 15w = 9w (-3 + 9w + 30w2) = 0 Solving -3 + 9w + 30w2 = 0 Solving for variable 'w'. Factor out the Greatest Common Factor (GCF), '3'. 3(-1 + 3w + 10w2) = 0 Factor a trinomial. 3((-1 + -2w)(1 + -5w)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-1 + -2w)' equal to zero and attempt to solve: Simplifying -1 + -2w = 0 Solving -1 + -2w = 0 Move all terms containing w to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -2w = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -2w = 0 + 1 -2w = 0 + 1 Combine like terms: 0 + 1 = 1 -2w = 1 Divide each side by '-2'. w = -0.5 Simplifying w = -0.5Subproblem 2
Set the factor '(1 + -5w)' equal to zero and attempt to solve: Simplifying 1 + -5w = 0 Solving 1 + -5w = 0 Move all terms containing w to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -5w = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -5w = 0 + -1 -5w = 0 + -1 Combine like terms: 0 + -1 = -1 -5w = -1 Divide each side by '-5'. w = 0.2 Simplifying w = 0.2Solution
w = {-0.5, 0.2}
| 4(s-1.4)=2 | | 3g-2=1 | | (2*x)*x=50 | | h=-16t^2+138t+82 | | 9x+14X+12X+115=360 | | 180=3x-2+4x-18+x | | 20+0.15t=30+10t+25 | | 57=29-4(x-4) | | -1x^2-4x-1=0 | | 2b+4.1=2.9 | | 3(a-6)+9(7-a)= | | -148+8x=41-x | | h=-16t^2+138+82 | | (5x+2y)squared=2 | | -16t^2+104t+56=104 | | .05(70x+100)-50=.04(90x+200)+50 | | 6x=14+16 | | 2(4y-1)-3y=12 | | 1.25r+6.75=31.75 | | 4x+-7x=13 | | -7-7k=-7(1+k) | | -2(m-3)=-6m | | 8(x+1)+11.6=9 | | 3m+1=6m-8 | | 3.5*x=x+0.5 | | 7a-9a=48 | | 3u-8=-17 | | -7=3d+11 | | (4xy+7)(4xy-7)=0 | | 76=3(-6n-5) | | A=7x+32 | | 3x+15-9=2x+2 |